2015
DOI: 10.1080/13607863.2015.1102196
|View full text |Cite
|
Sign up to set email alerts
|

Do determinants of burden and emotional distress in dementia caregivers change over time?

Abstract: This epidemiological and cross-sectional study describes the burdens and emotional distress observed among caregivers of elderly people. It was carried out in 2009 with 124 caregivers living in the city of Ribeirao Preto, SP, Brazil, using the following instruments: the Zarit Burden Scale and the Self-Reporting Questionnaire (SRQ-20) for caregivers. Data analysis was carried out in the SPSS, version 15.0, using descriptive, univariate (frequency tables) and bivariate (contingency tables for qualitative variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 25 publications
2
44
1
1
Order By: Relevance
“…Traditionally, studies have explored NPS using summative scores, and previous studies have found that caregiver burden increases along with the frequency and severity of CR NPS. 1 However, other studies have shown that FC psychosocial factors had a greater contribution to FC distress than NPS frequency. 14 A more nuanced approach to identify the most detrimental NPS to FC outcomes is needed.…”
mentioning
confidence: 94%
“…Traditionally, studies have explored NPS using summative scores, and previous studies have found that caregiver burden increases along with the frequency and severity of CR NPS. 1 However, other studies have shown that FC psychosocial factors had a greater contribution to FC distress than NPS frequency. 14 A more nuanced approach to identify the most detrimental NPS to FC outcomes is needed.…”
mentioning
confidence: 94%
“…9,10 However, it is unclear whether older UK AF veterans also have alcohol consumption problems, although a recent review found alcohol use disorders were more prevalent in geriatric US veterans compared with the general population. 13,14 Nonetheless, in spite of the above challenges, military service may also have lasting benefits, such as increased self-discipline, high levels of social support, and the improved ability to cope with adversity. 11,12 Mental health difficulties can be a source of distress both for older veterans and their families, impacting negatively on their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The caregiver is commonly female, of rather low education, living with the care recipient, spends a lot of hours caregiving and thus, they seem to have their emotional, physical, social and financial needs unfulfilled [8]. In line with other research, caregivers often report high levels of stress which affects them by feelings of low self-esteem, low sense of well-being, depression, sense of burden, compromised physical health and sometimes premature death [9,10,11]. Apart from psychological problems, social relationships change and psychosocial health may cause immunological dysfunctions to caregivers [12].…”
Section: Introductionmentioning
confidence: 71%
“…Apart from psychological problems, social relationships change and psychosocial health may cause immunological dysfunctions to caregivers [12]. Consequently, despite the fact that some caregivers experience feelings of personal gain and satisfaction, they need psychosocial and instrumental support to cope with caregiving [9,13].…”
Section: Introductionmentioning
confidence: 99%